Facile synthesis of porous cobalt oxide microplates and their lithium ion storage properties. (October 2014) - Che, H.; Liu, A.; Liu, C.; Jiang, R.; Fu, Q.; Wang, C.; Wang, L.
Abstract : Porous cobalt oxide (Co3 O4 ) microplates have been successfully synthesised via a facile thermal decomposition from plate-like cobalt oxalate complex precursors. The microstructures and morphologies of the obtained Co3 O4 materials are characterised by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and N2 adsorption–desorption techniques. The characterisation results show that the obtained Co3 O4 microplates are composed of plate-like polycrystalline nanoparticles with lengths of ∼20 nm and widths of ∼10 nm. In addition, these nanoplates aggregate each other to form the porous network with an average pore size of ∼18·9 nm. The obtained porous Co3 O4 microplates exhibit high discharge–charge capacities and good rate performances, suggesting a promising application as anode materials for Li ion batteries.